Responsiveness of Wii Fit Balance Board to the change after physical therapy and rehabilitation of lower limb lymphedema following thigh liposuction - El Sayed, Dalia Galal (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of this study was to measure and calculate the responsiveness of the Wii Fit Balance Board after physical therapy and rehabilitation of patients with lower limb lymphedema following thigh liposuction. The design of the study was a non – experimental, observational study. Sixty-three female patients with lymphedema following thigh liposuction, with a mean age of 51.2 years and who were undergoing physical therapy and rehabilitation, participated in this study. The Wii Fit Balance Board was used as a study instrument. Participants were asked to stand on the Wii Fit Balance Board (feet without sleeves), using skiing games for 10 seconds and 2 weeks apart after physical therapy treatment; the sixty-three patients were asked to do the same task again. The first score and second score were recorded respectively. Responsiveness of the Wii Fit Balance Board was measured by utilizing the standardized response mean (SRM) and the effect size (ES). Our study results showed that the Wii Fit Balance Board has an excellent responsiveness after physical therapy and rehabilitation of patients with lower limb lymphedema following thigh liposuction, as observed by ES and SRM values of 1.3 and 1.4 respectively. In conclusion, the Wii Fit Balance Board has a large degree of responsiveness after the physical therapy and rehabilitation program for patients with lymphedema following thigh liposuction.